1994
DOI: 10.1007/bf02090212
|View full text |Cite
|
Sign up to set email alerts
|

Motilin agonist erythromycin increases human lower esophageal sphincter pressure by stimulation of cholinergic nerves

Abstract: During phases II and III of the migrating motor complex, there is an increase in plasma motilin level that is synchronous with phasic and tonic contractile activity of the lower esophageal sphincter and of the stomach. The action of motilin on human lower esophageal sphincter is proposed to be mediated by cholinergic mechanisms. Recently, it has been shown that erythromycin was a motilin agonist. This study evaluated the pharmacological effects and the mechanisms of action of intravenous erythromycin on esopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 17 publications
0
31
0
Order By: Relevance
“…That increase in LES pressure occurred acutely (within 1–2 min); a similar result was seen in the present study. Other studies have shown that the increase in LES pressure due to motilin receptor agonists is cholinergically mediated [12, 13]. …”
Section: Discussionmentioning
confidence: 99%
“…That increase in LES pressure occurred acutely (within 1–2 min); a similar result was seen in the present study. Other studies have shown that the increase in LES pressure due to motilin receptor agonists is cholinergically mediated [12, 13]. …”
Section: Discussionmentioning
confidence: 99%
“…Neural regulation comes mainly from the sympathetic and parasympathetic nerves, which exert their effects by affecting corresponding receptors including muscarinic, α‐ and β‐adrenergic, and DA receptors. A variety of foods, drugs and pathologic factors also influence the LES through these four receptors 15,16 . It has been demonstrated that the excitation of the vagus nerve plays an important role in the formation of the HPZ of the LES by controlling the release of Ach 17,18 .…”
Section: Discussionmentioning
confidence: 99%
“…While a direct effect of both agents on enteric protein secretion cannot be definitely ruled out, it seems a highly unlikely explanation. Despite the fact that another macrolide antibiotic (erythromycin) has been reported to directly influence enteric motility [26, 27], to our knowledge no such data have been published for clarithromycin. In addition, no direct antisecretory properties of metronidazole have been described.…”
Section: Discussionmentioning
confidence: 71%